Extreme virtue : truth and leadership in five great American lives - Sartwell, Crispin, 1958- (Book collections on Project MUSE., 2003)
"Extreme Virtue presents a new and radical approach to the problems of leadership and virtue in public life. Originating in the author's newspaper writing about the Clinton/Lewinsky scandal, the book grapples with what has gone wrong in the American political system and describes what we should look for in our leaders and that more can be accomplished by straight talk than by polling and focus groups."--Jacket